Development of an institutionalised riot system in Meerut city, 1961 to 1982 - Brass, Paul R. (2004)
Meerut city in Uttar Pradesh has been a site of endemic Hindu-Muslim riots since before independence. In an attempt to explain the `institutionalised systems of riot production (IRS)' that are first created and then activated during periods of political mobilisation or at the time of elections, this article focuses on two riots in Meerut that occurred in post-independence India and were divided by a gap of 20 years. The 1961 riot is posed as a benchmark to contrast with later communal events of 1982, to illustrate the changes - more tense and deadly - that took place in the intervening period and to explain how and why these changes took place. - Reproduced.
Keywords: Riots - India - Uttar Pradesh; Riots